Fabrication of Light‐Weight and Highly Conductive Copper–Carbon Nanotube Core–Shell Fibers Through Interface Design. Issue 19 (7th August 2020) - Daneshvar, Farhad; Chen, Hengxi; Zhang, Tan; Sue, Hung‐Jue
Abstract: Metal‐carbon nanotube (CNT) hybrid fibers are emerging materials for light‐weight conductors that can replace common metallic conductors. One of the main challenges to their development is the poor affinity between CNT and metals. In this work, a new approach for fabrication of CNT/Cu core‐shell fibers is demonstrated that outperforms the commercial Cu wires in terms of specific conductivity, ampacity, and strength. By introducing thiol groups to the surface of CNT fibers, a dense Cu coating with enhanced adhesion is obtained. Consequently, CNT/Cu core‐shell fibers with specific conductivity of 3.6 × 10 7 S m −1 and tensile strength of 1 GPa, which is almost five times higher than commercial Cu wires, are produced. Due to strong interaction of thiol functional groups and Cu atoms, the fiber can preserve its integrity and conductivity after >500 fatigue bending cycles. Furthermore, the ampacity of the composite wire reaches to 1.04 × 10 5 A cm −2, which corresponds to a specific ampacity two times higher than that of commercial Cu wires. The interfacial design between Cu and CNT presented here is versatile and can be implemented in other processing and deposition methods. Abstract : In this work, carbon nanotube‐copper (CNT/Cu) core‐shell fibers are fabricated that outperform commercial copper wires in terms of mechanical and electrical properties. This is achieved through enhancing the Cu and CNT interactions by introducing short‐chain cysteine groups to their interface. These lightweight fibers are promising candidates for applications where weight reduction is desired including aerospace and portable electronics.